Neurocognitive predictors of adaptive functioning trajectories among youth with spina bifida. Issue 4 (19th May 2021) - Winning, Adrien; Stern, Alexa; Rausch, Joseph R.; Starnes, Meredith; Holmbeck, Grayson N.
ABSTRACT: Little is known about how youth with spina bifida (SB) acquire adaptive functioning skills across development. Therefore, the current study examined: (1) trajectories of adaptive functioning in youth with SB as they transitioned from childhood into adolescence, and (2) neuropsychological functioning as a potential risk factor for long-term adaptive functioning difficulties. Participants (n = 131 youth with SB) were recruited as part of a larger ongoing longitudinal study. Growth curves were used to examine changes over time across six adaptive functioning skills: communication, self-direction, functional academics, social, self-care, and home living skills. Additionally, youth's attention and executive functioning (i.e., working memory, planning/organizational skills, cognitive flexibility, inhibition) were assessed via questionnaires and performance-based assessments, and entered as predictors in the models. Youth's communication, self-direction, functional academics, self-care, and home living skills increased over time across age, whereas youth's social skills did not. Scaled scores for youth's social, communication, self-direction, and functional academics skills were generally within normal limits, whereas those for self-care and home living skills fell in the borderline range. Better attention and executive functioning predicted a higher intercept for many adaptive functioning abilities at 11.5 years old, above and beyond the influence of IQ. However, these variables did not predict growth in adaptive functioning. Results indicate that youth with SB acquire skills across development to better meet the demands of daily life. However, youth with poorer neurocognitive functioning may demonstrate adaptive functioning deficits in early childhood and benefit from timely intervention.